Innocent in Death - Robb, J. D. 1950- (New York : Berkley Books, 2007)
Investigating the baffling murder case of an ordinary and much-loved private school teacher, New York City lieutenant Eve Dallas struggles to identify who may have wanted the death of an innocent man.
Originally published: New York : G.P. Putnam's Sons, 2007.
Keywords: Fiction